Climate change threats to a floral wedding: Threats of shifting phenology to the emerging South African wedding industry - Fitchett, Jennifer; Mahlangu, Mazozo M. (Bulletin of Geography. Socio-economic Series, 2019)
Wedding tourism is a fast emerging niche market both globally and in South Africa, as destination weddings are becoming increasingly popular. Wedding industries across the world, and specifically in South Africa, are increasingly dependent on the natural environment. Wedding venues with floral gardens, farms, orchards or forests are particularly popular. Beyond the venue, flowers are important for the bouquets and decoration, with popular blooms changing year on year. Shifting phenology – the timing of annually recurrent biological events – has been identified as one of the most sensitive responses to climate change. This poses a threat to the sustainability of floral wedding venues and the floral industry relating to weddings. This exploratory study utilizes an interdisciplinary mixed-method approach to record the importance of flowers in South African weddings and the perceived threats of climate change to this subsector. The respondents reveal the importance of flowers and the outdoors in both symbolism and the enjoyment of the wedding day, and had organised their wedding date to align with flowering. Destinations highlight a lack of awareness regarding phenological threats and are relatively unperturbed about the threats of climate change. Comparison to global phenological shifts reveals that these are misplaced. There is, therefore, a need for such wedding venues to adopt adaptive strategies to preserve their environment which drives wedding tourism.